Gambaran Kadar Asam Urat Pada Pria dengan Kebiasaan Mengonsumsi Minuman Beralkohol Di Desa Noongan II Kecamatan Langowan Barat - Sumual, Chlifano Esau; Katuuk, Mario Esau; Mulyadi, Mulyadi (Mapalus Nursing Science Journal, 2023)
Background: The habit of consuming alcoholic beverages can increase the level of uric acid. Alcohol can disrupt uric acid metabolism in the body, leading to excessive uric acid accumulation. Objective: This study aims to determine the levels of uric acid in men with a habit of consuming alcoholic beverages in Noongan II Village, West Langowan District. Methods: This study utilized a descriptive research design. The sample consisted of 78 participants selected through non-probability purposive sampling technique. Results: Out of the total 78 blood samples examined, it was found that 53.6% had high uric acid levels or hyperuricemia, while 47.4% had normal uric acid levels. Discussion: This study discusses the relationship between alcohol consumption and uric acid levels, including the duration, frequency, and volume of consumption. Conclusion: The study shows that a majority of the respondents experienced hyperuricemia, and this finding is associated with several alcohol consumption factors. Specifically, it was found that individuals who consumed alcohol for more than 5 years, consumed alcohol frequently, and consumed alcohol in large volumes, all experienced hyperuricemia